Pengaruh Myofascial Release Terhadap Nyeri Spasme Otot Upper Trapezius Pada Ibu Rumah Tangga Di Rt.03 BringinBendo, Kec. Taman Sidoarjo - Cesario Prima Rahmadani; Angria Pradita; Rachma Putri Kasimbara; Sartoyo Sartoyo (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: The goal is to release the restrictions that create obstructions in the deeper layers of the fascia. This is achieved by stretching the elastic components of the fascia muscles, together with cross ties and changing the basic substance of the fasciaa (Shah et al., 2012) in housewives' complaints when working for a long time such as sewing, cooking in a long crouching position Musculoskeletal disorders like this  If left untreated, it can cause the strength of the neck muscles to decrease so that it has an impact on decreasing productivity, increasing the risk of work-related diseases and losing time (Wahyono, Saloko, 2014).Methods: This study used a pre-experiment with one group of pre- and post-test respondents, totaling 15 people woman. with purposive sampling technique, data collection using the NRS test. Normality test using Univariate and bivariate tests followed by data analysis using.Results: measurement using the NRS pain meter on patient complaints of upper trapezius muscle spasm pain and interventions giving myofascial release. examination was taken during the post-test examination after that there was a change in the decrease in spasm pain of the upper trapezius muscle and the results of test the hypothesis by showing the distribution of data on the normality value of significance p< 0.05Conclusion: Giving myofascial release has proven to be effective in reducing muscle spasms and restoring the elasticity of the fascia muscles